E-learning in the Teaching-Learning of Distance Higher Education: A Review (LACCEI, 2024)
Currently, higher level educational institutions are linked to the internet and ICTs as a consequence of the COVID-19 state of health emergency, the purpose of the study was to analyze e-learning in teaching-learning in distance higher education. The main theoretical approaches, strategies and tools used in the teaching-learning of the engineering career at a higher level were identified. The systematic review of scientific articles was used with the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) method applied the approach (PRISMA) Applying the Kitchenham approach. The search strategy consisted of choosing the databases: Scopus, Web of Science and Scielo with the use of Boolean operators (AND, OR) to perform unions or combinations with the previously chosen keywords and descriptors. The final result obtained 38 articles published between 2019 and 2023. Conclusions: regarding the theoretical model, 18 articles have been used, 26 articles were analyzed on the most frequent strategies and 26 were determined regarding the tools used by teachers and students, within the impact conclusions it has been inferred that appealed to the use of different models and strategies for teaching-learning based on e-learning, using online digital and audiovisual tools as the main tools.